Adherence factors on pharmacological and non-pharmacological treatment in chronic kidney disease patients - Méndez-Ortega, Ocotlán; Hernández-Vicente, Irma Alejandra; Juárez Flores, Clara Arlina; Lumbreras-Delgado, Irma; Banderas Tarabay, José Antonio (Horizonte Sanitario, 2023)
Objective: To evaluate the influencing factors that affect the adherence to the treatment in chronic kidney disease patients.Material and Methods: A descriptive cross-sectional study was carried out in a sample size of 80 patients in an external nephrology service from a hospital at Tlaxcala. A previously validated questionnaire divided in four dimensions was used to determine the factors that influence patients to maintain pharmacological and non-pharmacological adherence to their treatment.Results: A moderate risk level of adherence was present in this population, el 8.8% of the patients have adherence to the treatment, el 58.8% are in moderate risk of non-adherence, and 32.5% have a high risk of no adherence. The main factors by no adherence are lack of economic sources (65%), unknown their dry weight (61.3%), a highcost dietetic regime (60%), having difficulties to change their live style (38.8%), and do not get information about their medicine advantages (8.8%).Conclusions: Lack of moneyand information are the influencing factors because the patient do not have adherence to the pharmacologic and non-pharmacologic treatment. The nursing professional should provide clear, useful and complete information in order to improve the treatment adherence, to reduce complications and costs in CKD patients. It is necessary to look forward for educative and motivational strategies because their economic situation and arraigned habits, looking for social and family support to improve their health status. Key words: Accomplish; Treatment adherence; Socioeconomic factors; Chronic kidney disease.